menu
bartleby
search
close search
Hit Return to see all results

For f(x) 1-x and g(x)= 2x +x+6, find the following functionsa. (f o g)(x): b. (gof)(x); c. (fo g)2), d. (g o f)(2)a. (fo g)x)(Simplify your answer.)ranser in the ansrer box and then cick check AnswerparisremainingCopyright @ 2019 Pearson Edu

Question
For f(x) 1-x and g(x)= 2x +x+6, find the following functions
a. (f o g)(x): b. (gof)(x); c. (fo g)2), d. (g o f)(2)
a. (fo g)x)
(Simplify your answer.)
ranser in the ansrer box and then cick check Answ
er
paris
remaining
Copyright @ 2019 Pearson Edu
help_outline

Image Transcriptionclose

For f(x) 1-x and g(x)= 2x +x+6, find the following functions a. (f o g)(x): b. (gof)(x); c. (fo g)2), d. (g o f)(2) a. (fo g)x) (Simplify your answer.) ranser in the ansrer box and then cick check Answ er paris remaining Copyright @ 2019 Pearson Edu

fullscreen
check_circleAnswer
Step 1

Answer: (a): -2x^2-x-5

(fog) (x)
=f[g(x)]
=f (2x2+x+6)
=1-(2x2+x+6)
—1-2х*-х-6
--2x-х-5
help_outline

Image Transcriptionclose

(fog) (x) =f[g(x)] =f (2x2+x+6) =1-(2x2+x+6) —1-2х*-х-6 --2x-х-5

fullscreen
Step 2

Answer(b): 2x^2-5x+9

(gof) (x)
-g[f (x)]
=g(1-x)
2(1-x)2+(1-x)+6
2(1-2x+x21-x+6
-2-4x+2x2-x+7
-2x2-5x+9
help_outline

Image Transcriptionclose

(gof) (x) -g[f (x)] =g(1-x) 2(1-x)2+(1-x)+6 2(1-2x+x21-x+6 -2-4x+2x2-x+7 -2x2-5x+9

fullscreen
Step 3

Answer(C): ...

(fog) (2)
=-2(2)2-2-5
=-8-7
=-15
help_outline

Image Transcriptionclose

(fog) (2) =-2(2)2-2-5 =-8-7 =-15

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Our solutions are written by experts, many with advanced degrees, and available 24/7

See Solution
Tagged in

Math

Algebra

Other

Sorry about that. What wasn’t helpful?